Determinants of technology-based SMEs’ ability to attract talent with a Master’s degree: Case study of a city in Northeast China - Guohong Chen; Lu Xu (PLoS ONE, 2025)
Talents with a master’s degree have high-level professional skills and knowledge reserves. They play an important role in overcoming the traditional technological bottlenecks of technology-based small and medium-sized enterprises (SMEs). Taking Shenyang in Northeast China as an example of a talent outflow city, we begin by considering the attraction of technology-based SMEs’ operations to talent with a master’s degree or above. We then use correlation analysis and gray correlation analysis to analyze the influence of technology-based SMEs’ operations on attracting talent with a master’s degree as well as the correlation and correlation degree between the factors. The results show that the number of talents with a master’s degree or above in technology-based SMEs is significantly positively correlated with number of employees (X9), total assets (X3), total tax paid (X7), main business income (X5), total indebtedness (X4), and total profit (X6). These indicators are the determinants of technology-based SMEs’ ability to attract talent with a master’s degree. These results are consistent with the correlation and gray correlation analyses; thus, the results are mutually verified using two different approaches. Recommendations for talent-attraction policies in technology-based SMEs include strengthening the attraction and training of scientific and technological innovation talent, appropriately optimizing assets and liabilities, enhancing core business innovation and development, and promoting steady growth in profit tax payments. Our findings provide a basis for authorities to develop effective strategies and policies to help SMEs attract talent with a master’s degree.